A Guide to Marxian Political Economy What Kind of a Social System Is Capitalism? - Otani, Teinosuke (Springer International Publishing, 2018)
This textbook offers a comprehensive guide to the systematic structure of capitalism, while at the same time introducing readers to all three volumes of Marx's Capital. Based on his extensive expertise on Marx's critique of political economy, the author reveals the specific structure of production in capitalist societies and explicates what sets this system apart from other modes of production. Marx's political economy is explained in a systematic and easy-to-understand manner, using numerous illustrative diagrams to complement the text. This textbook will appeal to all students and scholars looking for a more comprehensive, systematic and theoretical explanation of capitalism, equipping them with a solid theoretical understanding of its core structure. .